PROCESSING OF THE GOLD ORE FROM KEDONDONG AREA, SOUTH LAMPUNG USING GRAVITY CONCENTRATION METHOD - Lili Tahli; Tatang Wahyudi (Puslitbang tekMIRA, 2013)
Kedondong gold ores seem promising to be processed. Referring to its mineralogy characters, the ores can be treated by gravity concentration method that include Knelson concentrator, shaking table, jig and sluice box as well. Processing the gold sample coded A from Kedondong, South Lampung by Knelson concentrator increased the Au grade from 21.87 to 399.76 g/t. Its recovery was 91.57 %. The silver grade also improved from 287.83 to 3,427.12 g/t performing recovery of 49.65 %. Re-processing Knelson concentrator concentrates using shaking table enlarged the Au and silver grades to 1,199.28 and 5,430.80 g/t respectively. Both Au and Ag recoveries were around 89.84% and 47.45% respectively. Another sample, coded B, provided grade 165.80 g/t Au (from 8.93 g/t) and 3,275.05 g/t Ag (from 172.73 g/t) when processed by Knelson concentrator. A shaking table process for such a B-Knelson concentrate yielded the Au and Ag grades to 710,05 and 13.800,80 g/t respectively and also improved the Au and Ag recoveries to 85.56 and 85.17%. Concentrate Sample A has satisfied the requirement for final processing using smelting method, however, Sample B still needs more shaking table process in order to get satisfied condition for smelting process, namely the grade of gold >1,000 g/t.